Evidence based service change: remodelling the academic libraries for the post-digital era - Laitinen, Markku; Saarti, Jarmo (Qualitative and Quantitative Methods in Libraries; Vol 3 No 3 (2014): September 2014 Issue, 2017)
During the past couple of decades, university libraries have changed their paradigm away from collection based services towards promoting the access and use of digital scientific resources. At the same time, evidence based library management techniques have been discussed widely. The need for adapting to the rapidly changing operational environment has meant that library management has had to change, now taking a more professional approach to making strategic and at the same time economically and professionally efficient decisions. This paper examines the role of library statistics on which to base library service redesign in one Finnish academic library. A special emphasis was placed on the trend analyses and the best way of presenting statistical data to the decision makers and how to conduct (inter)national level co-operation in the analysis and gathering of the statistics.